This Gaming Life : Travels in Three Cities - Rossignol, Jim, 1978- (Book collections on Project MUSE., 2008)
""In May 2000 I was fired from my job as a reporter on a finance newsletter because of an obsession with a videogame. It was the best thing that ever happened to me." So begins this story of personal redemption through the unlikely medium of electronic games. Quake, World of Warcraft, Eve Online and other online games not only offered author Jim Rossignol an excellent escape from the tedium of office life. They also provided him with a diverse global community and a job--as a games journalist. Part personal history, part travel narrative, part philosophical reflection on the meaning of play, This Gaming Life describes Rossignol's encounters in three cities: London, Seoul, and Reyjkavik. From his days as a Quake genius in London's increasingly corporate gaming culture; to Korea, where gaming is a high stakes televised national sport; to Iceland, the home of his ultimate obsession, the idiosyncratic and beguiling Eve Online, Rossignol introduces us to a vivid and largely undocumented world of gaming lives. Torn between unabashed optimism about the future of games and lingering doubts about whether they are just a waste of time, This Gaming Life also raises important questions about this new and vital cultural form. Should we celebrate the "serious" educational, social, and cultural value of games, as academics and journalists are beginning to do? Or do these high-minded justifications simply perpetuate the stereotype of games as a lesser form of fun? In this beautifully written, richly detailed, and inspiring book, Rossignol brings these abstract questions to life, immersing us in a vibrant landscape of gaming experiences."--Publisher's description